Gender Differences in the Use of Hedging devices in Students’ Conversations - Ratna Trihartanti (Jurnal Bahasa Inggris Terapan, 2020)
To minimize conflict that might happen during conversation, and one of the tools is hedging. In fact, there are some differences in using hedging between female and male students; therefore, this study is conducted with aims: first is to identify what types of hedging used by female and male students, and the second is to analyze gender differences in using hedging, and the third is to analyze the function of hedges used by students. This research uses a qualitative method and the data taken from 24 female students of the English department, and 24 students of Electrical engineering. Having been analyzed, it could be found out that hedges used by female English students are: plausibility shields (30%), rounders (15%), adaptors (7%) attribute (4%) including hedges taken from negative politeness strategy such as: question, hedge (10%), and the imposition, Rx is (7%). The last hedges often used as discourse markers are: ‘Hmm’ (10%), ‘Well’ (7%) and ‘Oh’ (6%). On contrast, male students mostly applied hedges: plausibility shields (12%), rounders (5%), adaptor (4%), attribute (4%). from negative politeness strategy, question, hedge to express politeness by using indirect question (7%), and the imposition, Rx to decrease the imposition of utterance (4%). Male students also apply some discourse markers as hedges such as: ‘well’ (12%), ‘Oh’ (6%) and ‘Hmm’ (5%). From the research it is also found that female students often show their hesitations, use long utterances while male students try to show their self-confidence, and they mostly utter to the point.